Extracção e purificação de 3 - (3,4-diidroxifenil) alanina a partir das sementes de stizolobium aterrima - Ujikawa, Keidi [UNESP] (My University, 1998)
A process for extraction and purification of L-3-(3,4 dihydroxyphenyl)alanine from seeds of Stizolobium aterrima was developed. The seeds extract was obtained by a new process and concentrated to obtain the product. The product was purified by two processes. The advantages of the methods are elimination of one operation, greater facility of filtration of the extract and greater purity of the product. Nowadays the process may have academic interest for class demonstrations.
Keywords: Extraction and purification; L-3-(3,4-dihydroxyphenyl)alanine; Stizolobium aterrima; levodopa; plant extract; drug isolation; drug purification; filtration; plant seed